Recycling flower waste to humus rich compost using effective microbial consortium and mechanical intervention - LIVLEEN SHUKLA; SATISH D LANDE; ROAF AHMAD PARRAY; ARCHNA SUMAN; K ANNAPURNA; INDRA MANI; VIKRAM VIKRAM (The Indian Journal of Agricultural Sciences, 2019)
The importance of organic manure as soil amendment is increasing day by day especially for the improvement of soil health. Flower waste has a high moisture content and easily degradable carbon content. A long duration leachate and odour problem arises during accumulation of flowers. The study aimed on changes in the physico-chemical parameters during the pit method composting of flowers using effective microbial consortium. Four different composting mixturemarigold flower waste + Dried Leaves (1:1), Marigold flower waste + Dried leaves (1:1) + Microbial consortium, Rajnigandha flower waste + Dried leaves(1:1) and Rajnigandha flower waste + Dried leaves (1:1) + Microbial Consortium were prepared. Results revealed that the temperature profile in all the treatments in cemented pits showed a rapid procedure from ambient temperature of 32ºC to 55ºC. The maximum temperature obtained was 55ºC within six days in the pits and pH varied from 4.5 to 5.5 and after 30 days it was found to be 7.0. The measurement of humus content was observed more in the treatments where fungal inoculants were applied as compared to un-inoculated treatments. The final product was rich in carbon, nitrogen content and was found non-phytotoxic.